Synthesis and application of an alkaline crosslinking agent containing acrylamide as the durable press finishing agent on cotton fabric. Issue 11 (June 2019) - Li, Fuqiang; Wang, Hongchen; He, Jinxin
In this study, acrylamide-containing crosslinking agents 2, 4-diacrylamidebenzenesulfonic acid (AC-DABS1) and 2, 5-diacrylamidebenzenesulfonic acid (AC-DABS2) were synthesized and applied to cotton fabric as durable press finishing agents under alkaline conditions. The target products were characterized by high-performance liquid chromatography (HPLC) and proton nuclear magnetic resonance. The stability of the acrylamide group in alkaline solution was investigated by model compound para-acrylamidebenzenesulfonic acid. The efficiency of AC-DABS1 and AC-DABS2 as durable press finishing agents was examined and compared by testing the wrinkle recovery angle (WRA), tearing strength retention (TSR) and washing durability under different conditions using the steaming process. The performance of fabric treated with 1, 3, 5-triacroylaminohexahydro-s-triazine (FAP) was also investigated and compared with those treated with acrylamide-containing crosslinking agents. The results showed that the anti-crease effects of FAP were better than those of the new synthesized agents. However, the new synthesized agents have the advantage of water solubility and low cost. The fabric treated with new synthesized agents presented satisfactory WRA and TSR, indicating that AC-DABS1 and AC-DABS2 can be utilized as effective alkaline crosslinking agents. In addition, the different performance of the FAP-treated fabric and fabric treated with the new synthesized agents was illustrated by the HPLC method.